Durability of Viral Neutralization in Asymptomatic Coronavirus Disease 2019 for at Least 60 Days. (15th March 2021) - Haymond, Amanda; Damluji, Abdulla A; Narayanan, Aarthi; Mueller, Claudius; Reeder, Alex; Alem, Farhang; Maxwell, G Larry; Petricoin, Emanuel F; Liotta, Lance; deFilippi, Christopher R
Abstract: A cohort consisting of asymptomatic healthcare workers donated temporal serum samples after infection with severe acute respiratory syndrome coronavirus 2. Analysis shows that all asymptomatic healthcare workers had neutralizing antibodies, that these antibodies persist for ≥60 days, and that anti-spike receptor-binding domain immunoglobulin G levels were correspondingly durable over the same time period. Abstract : Asymptomatic healthcare workers infected with severe acute respiratory syndrome coronavirus 2 show durable viral neutralization titers from baseline to 60 days with a BSL-3 viral plaque reduction neutralization test. Anti–receptor-binding domain immunoglobulin G is also durable during this time.